THE ROLE OF THE GENERAL ELECTION COMMISSION IN INCREASING THE PARTICIPATION OF PERSONS WITH DISABILITIES IN THE 2024 REGIONAL HEAD ELECTIONS OF MOJOKERTO CITY - santosa santosa; Nabil Hoesny Basalamah (MAJAPAHIT POLICY, 2025)
The implementation of elections in Indonesia is the responsibility of the General Elections Commission (KPU), the sole institution appointed by the government to organize general elections. The KPU is responsible for ensuring that the general election process runs smoothly and appropriately for all Indonesians. This research focused on the KPU's role in regional head elections for persons with disabilities in 2024. The descriptive qualitative method chosen by the researcher in conducting this research allows the researcher to describe various existing phenomena in greater depth. Through the use of Thomas and Briddle's theory on roles, this study concluded that the role of the Mojokerto City General Elections Commission (KPU) in addressing persons with disabilities in the 2024 regional head elections was successful and in accordance with its role indicators. This research is expected to lead to continuous improvements from the KPU in organizing elections for persons with disabilities in the future.